Fernanda Beigel (ed.): The Politics of Academic Autonomy in Latin America - Hanafi, Sari (Serendipities. Journal for the Sociology and History of the Social Sciences, 2016)
Book Review of: Fernanda Beigel (ed.) The Politics of Academic Autonomy in Latin America Farnham: Ashgate 2013 Hardcover, 290 pp. ISBN 9781409431862 Price: € 120